Lepeostegeres cebuensis (Loranthaceae), a new mistletoe species from Cebu, Philippines - Pelser, Pieter B.; Nickrent, Daniel L.; Reintar, Andrew R. T.; Barcelona, Julie F. (Phytotaxa, 2016)
Lepeostegeres cebuensis is described as a new species from Cebu Island, Philippines. It is unique among currently known species in the genus by having peculiar ridges of orange-brown scales on the young leaves and internodes. This discovery brings the total number of Philippine Lepeostegeres species to three. We consider Lepeostegeres cebuensis to be Data Deficient (DD) following the Red List Criteria of the International Union for the Conservation of Nature (IUCN).